Fundamental Pillars of Islamic Education Management: A Conceptual Framework for Strengthening Islamic Educational Institutions in the Modern Era - Kholidah Hannum Hasibuan; Zulhimma Zulhimma (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Islamic education management has a strategic role in integrating spiritual values with modern managerial principles to strengthen the quality of Islamic educational institutions. This article aims to conceptually examine the five fundamental pillars of Islamic education management, namely value-based planning, prophetic leadership, adaptive Islamic curriculum, holistic human resource development, and character-oriented evaluation. This study uses a qualitative approach with a library research method. The data sources in this study are 17 secondary sources, including scientific books and reputable national and international journal articles from 2012 to 2025 that are relevant to the theme of Islamic education management. Data was searched using the Publish or Perish application with purposive sampling, i.e., only literature relevant to the five main pillars of the study, namely value-based planning, prophetic leadership, adaptive Islamic curriculum, holistic human resource development, and ethics-oriented evaluation, was used as material for analysis. Data search was conducted using the Publish or Perish application. The results of the study indicate that strengthening these five pillars is the main foundation in developing an integrative Islamic education management that is relevant to the demands of the modern era. The integration of spirituality and rationality in the management of Islamic educational institutions is central to the formation of a generation with excellent character, professionalism, and noble morals. This study emphasizes the importance of the conceptual framework of Islamic education management as the basis for developing managerial strategies that are adaptive to global transformation without abandoning Islamic identity.